Double star induction machine using nonlinear integral backstepping control - Abden Abdallah; A. Bouchetta; O. Boughazi; A. Baghdadi; L K. Bousserhane (Institute of Advanced Engineering and Science, 2019)
This paper presents a nonlinear Integral backstepping control approach based on field oriented control technique, applied to a Double Star Induction Machine ‘DSIM’ feed by two power voltage sources. We present this technique of integral backstepping by using reduced and complete Model of DSIM. The objective is to improve the robustness of machine under internal parameter variation with nonlinear Integral backstepping control. The robustness test results obtained by simulation prove the effectiveness of control with using complete model of DSIM.